Hukum Sujud Syukur Tanpa Berwudu menurut Mazhab Maliki dan Mazhab Syafi’i - Laila Azizah; Ruslan (Interdisciplinary Explorations in Research Journal, 2023)
Abstract As we know, prostration is a part that cannot be left behind in worshiping Allah Swt. With that, every prostration that we make in prayer contains something of the power to draw us closer to Allah Swt. There are many types of prostration in Islamic teachings, one of which is prostration of gratitude, some of these prostrations of gratitude require that you perform ablution first, there are also opinions that prostrations of gratitude do not require wudu. The Maliki School and the Syafi’i School have different views regarding whether to prostrate in gratitude without performing ablution first. One of the striking differences is that the Maliki School allows prostrations of thanks without performing ablution first, while the Syafi’i School states that prostrations of thanks must be in a state of ablution as is a valid requirement for prayer. The type of research that the author uses in this research is descriptive normative legal research using a comparative approach, which focuses on Islamic studies by examining Islamic law books, schools of Islamic jurisprudence books in particular as material for analysis. The results of this research show that the Maliki School and the Syaf’i School have different opinions regarding prostrating gratitude without performing ablution. The Maliki Absolute School states that there are no conditions before performing prostrations of gratitude. Meanwhile, in the Syafi’i School, before performing prostrations of gratitude, you must first be in a pure state. Regarding the istinbath method in adopting the law regarding prostration of gratitude without ablution, the Maliki School and the Syafi’i School both use authentic hadith arguments as the legal basis for prostrating gratitude without ablution. However, the Maliki School considers the hadith argument regarding prostration of gratitude to be ‘am’ so that to complete the prostration with wudu must require a sharih argument. Meanwhile, the Syafi’i School considers the argument of this hadith to be general because the hadith has ihtimal (possibility) and the hadith is still within the scope of Ijmal so one has to wait for the opinion to explain it Keywords: Law of Prostration of Gratitude, Without Wudu, Maliki School, Shafi’i School Abstrak Seperti yang kita ketahui sujud adalah bagian yang tidak akan tertinggal dalam beribadah kepada Allah Swt. Dengan itu pula setiap sujud yang kita lakukan di dalam salat itu di dalamnya ada sesuatu kekuatan untuk banyak-banyak mendekatkan diri kita kepada Allah Swt. Terdapat banyak macam sujud di dalam ajaran Islam, salah satunya adalah sujud syukur, sujud syukur ini ada yang mensyariatkan harus berwudu terlebih dahulu ada juga pendapat bahwa sujud syukur tidak perlu adanya wudu. Mazhab Maliki dan Mazhab Syafi’i memiliki pandangan berbeda mengenai sujud syukur tanpa berwudu terlebih dahulu atau tidak. Salah satu perbedaan mencolok adalah Mazhab Maliki membolehkan sujud syukur tanpa berwudu terlebih dahulu, sementara Mazhab Syafi’i menyatakan bahwa sujud syukur itu harus dalam keadaan berwudu sebagaimana syarat sah salat. Jenis penelitian yang penulis gunakan dalam penelitian ini adalah penelitian hukum normatif yang bersifat deskriptif melalui pendekatan komparatif, yang berfokus kepada kajian keislaman dengan menelaah buku-buku hukum Islam, kitab-kitab fikih mazhab khususnya sebagai bahan analisis. Hasil penelitian ini menujukkan bahwa Mazhab Maliki dan Mazhab Syaf’i memiliki perbedaaan pendapat tentang sujud syukur tanpa berwudu. Mazhab Maliki Mutlak menyebutkan bahwa tidak ada syarat sebelum melakukan sujud syukur. Sedangkan Mazhab Syafi’i sebelum melakukan sujud syukur harus dalam keadaan suci terlebih dahulu. Mengenai metode istinbath dalam pengambilan hukum tentang sujud syukur tanpa berwudu Mazhab Maliki dan Mazhab Syafi’i sama sama menggunakan dalil hadist sahih sebagai dasar hukum sujud syukur tanpa berwudu. Namun, Mazhab Maliki menganggap dalil hadis tentang sujud syukur itu ‘am’ sehingga untuk men-takhsis sujud dengan wudu itu harus memerlukan dalil yang sharih. Sedangkan Mazhab Syafi’i mengganggap dalil hadis tersebut menunjukkan umum karena hadis tersebut memiliki ihtimal (kemungkinan) dan hadis tersebut masih dalam lingkup Ijmal sehingga harus menunggu bayan yang menerangkannya Kata Kunci: Hukum Sujud Syukur, Tanpa Berwudu, Mazhab Maliki, Mazhab Syafi’i